The Impact of Dadih Functional Bread on Gestational Weight Gain for Pregnant Women in Padang, Indonesia: a Randomized Controlled Trial - Helmizar Helmizar; Azrimaidaliza Azrimaidaliza; Faza Yasira Rusdi; Asrawati Asrawati; Ferdinal Ferry (Amerta Nutrition)
Background: Gestational Weight Gain (GWG) is correlated to the growth and development of foetus and pregnancy outcomes. Probiotics have a positive effect on gestational weight gain. Dadih is a traditional West Sumatra food containing 108 CFU/ml of probiotics.